1992
DOI: 10.22358/jafs/69904/1992
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of biliary fat and fatty acids in growing pigs

Abstract: The aim of the present work was to study the contribution of bile secretion to endogenous excretion with special emphasis on the amount of fat and long chain fatty acids. A cannulation technique with a re-entrant cannulae via a duodenal pouch was developed for the purpose. With three growing pigs of 30 kg initial live weight several collections of bile were carried out over 24 hr periods. The average daily bile output was 1.8 1, but with high variations both between and within pigs. The concentration of total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Although the influence of endogenous FA (Jørgensen et al, 1992a) cannot be discarded, our results fully agree with other studies where biohydrogenation of unsaturated FA was observed (Jørgensen et al, 1992b;Reis De Souza et al, 1995;. It can be hypothesised that oleic (C18:1), linoleic (C18:2) and linolenic (C18:3) acids reaching the hindgut are, at least in part, saturated by the microflora and converted into stearic acid (C18:0), which would explain the lower digestibility coefficients (in some cases negative) at the faecal than at the ileal level observed for this FA.…”
Section: Resultsmentioning
confidence: 99%
“…Although the influence of endogenous FA (Jørgensen et al, 1992a) cannot be discarded, our results fully agree with other studies where biohydrogenation of unsaturated FA was observed (Jørgensen et al, 1992b;Reis De Souza et al, 1995;. It can be hypothesised that oleic (C18:1), linoleic (C18:2) and linolenic (C18:3) acids reaching the hindgut are, at least in part, saturated by the microflora and converted into stearic acid (C18:0), which would explain the lower digestibility coefficients (in some cases negative) at the faecal than at the ileal level observed for this FA.…”
Section: Resultsmentioning
confidence: 99%
“…Digestion of fat in poultry is to a large extent depending on bile salt secretion (Kussaibati et al 1982;Krogdahl 1985;Knarreborg et al 2003), and is a limiting factor for the micelle formation especially in young birds fed unsaturated fatty acids (Wiseman and Lessire 1987). The curvilinear pattern of fat digestibility shown in Table 3 demonstrates that endogenous fat originating from bile (Jørgensen et al 1992a), desquamated cells or exudation from the mucosa had higher impact on the apparent fat digestibility at low dietary fat levels than at higher levels (Jørgensen et al 1993). Expressing the intake of dietary fat on digested amount of fat in absolute amounts a linear relationship is revealed and the partial digestibility of fat can be found by regression (Jørgensen and Ferna´ndez 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The diets were formulated to be isoenergetic, and so rapeseed oil was added to medium-and high-fibre diets. The higher the ether extract content, the higher is the ileal and faecal apparent digestibility of ether extract (Jørgensen et al, 1992). The dietary organic acid mixture improved the faecal digestibility of ether extract, whereas it produced only a tendency towards improvement in ileal apparent digestibility.…”
Section: Figurementioning
confidence: 93%